ANALISIS PENGARUH WORD OANALISIS PENGARUH WORD OF MOUTH, KUALITAS LAYANAN, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS PADA TOKO BANDUNG SUPER MODEL DINOYO MALANG)F MOUTH, KUALITAS LAYANAN, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS PADA TOKO BANDUNG SUPER MODEL DINOYO MALANG) - Muh. Saifullah; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT Current economic developments encourage competition in various sectors, especially in the same type of business, namely retail. The tight of competition make businesses compete in increasing sales to obtain the expected profitability. Therefore, efforts are needed to increase the purchasing decisions of consumers. The purposed of this study was to analyze the influence of independent variables of word of mouth, the quality of service, product quality, and location through the dependent variable is a purchase decision.This research used primary data obtained from the distribution of questionnaires. The technique of sampling in this study using accidental sampling method. The number of samples obtained by 7.600 consumers Bandung Super Model stores located in Dinoyo Malang. Data analysis in this study using multiple linear regression techniques.The results of this study indicate that the variable word of mouth, the quality of service, product quality, and the location has a positive influence and significant on purchasing decisions to Bandung Super Model stores in Dinoyo Malang, either partially or simultaneously.Keyword : Word of mouth, service quality, product quality, location, purchasing decision